Missionários de letras e virtudes: a pedagogia moral dos franciscanos em Alagoas nos séculos XVIII e XIX - Santos, Mônica Costa (2007)
The present study considered the reconstitution of the educative action developed by the missionaries Franciscans north-eastern Brazilian, in the century s XVIII and XIX, for of the itinerant s missions and the convents of the Order distributed by the region. Our study it was turned, in special, toward the work carried through educative missionary and in the south part of the captainship of Pernambuco, over all from the construction of the two Franciscans convents in the alagoano territory, that had started to serve of base structural for the action of the missionaries. Carriers of a long religious and intellectual tradition, integrated to the colonial context, the Franciscans intended to evangelizer and to civilize the local population and of regions proximal, by means of its moral pedagogic, the end to make data profile of behavior, based on religious beliefs and civilized values. In this direction, faith and reason converged in one same direction, therefore at the same time where religious rules make themselves, also searched to still harmonize, to moralizer and to instruct members of a society in formation. For the elaboration of this study, in we support them in the consultation of works produced for the proper missionaries, the Acts Capitulates of the Franciscan Province of San Anthony of the Brazil (1649-1893) and Books of Chronicles of the Convents of Penedo/Alagoas (1903-1930; 1907-1920), beyond published correspondences and doubtful documents in periodic, and workmanships regarding San Francisco of Assis and of the Franciscans. We search spoon referring pedagogical traces the performance of the religious ones in Alagoas, for of an extended notion of education that understands the formation of habits and customs. Such values and rules were propagated in the different religious and educative activities carried through by the Franciscans, example of the lessons of grammar, the sermons, the saint s missions , the parties and celebrations, the processions and the images of saints and Franciscans saints. For frades of the order of San Francisco, the letters were the service of the apostolate, either in the preparation of the aspiring the religious life or in the make of the secular students. On the prescribed moral pedagogic for missionaries, identified that the same one was in accordance with the Franciscans beddings and principles, and with the project Portuguese of evangelization and civilization of the Brazilian population, restraining habits had as barbarous, stopping passions, calming rebellions, and adjusting to the behavior of those individuals to effective the religious and civil standards the time.